GCIG-Consensus guideline for Long-term survivorship in gynecologic Cancer: A position paper from the gynecologic cancer Intergroup (GCIG) symptom benefit committee. (June 2022) - Woopen, H.; Sehouli, J.; Davis, A.; Lee, Y.C.; Cohen, P.A.; Ferrero, A.; Gleeson, N.; Jhingran, A.; Kajimoto, Y.; Mayadev, J.; Barretina-Ginesta, M.P.; Sundar, S.; et al.
Highlights: Long-term survival with gynecological cancer was defined as survival of at least five years after diagnosis. More than 50% of long-term survivors still experience long-term side effects and other treatment-related health concerns. Follow-up should be offered lifelong. An example for a survivorship care plan including recommendations is included in the manuscript. Abstract: Introduction: Long-term survivors of gynecological cancers may be cured but still have ongoing health concerns and long-term side effects following cancer treatment. The aim of this brainstorming meeting was to develop recommendations for long-term follow-up for survivors from gynecologic cancer. Methods: International experts, representing each member group within the Gynecologic Cancer InterGroup (GCIG), met to define long-term survival, propose guidelines for long term follow-up and propose ways to implement long term survivorship follow-up in clinical trials involving gynecological cancers. Results: Long-term survival with/from gynecological cancers was defined as survival of at least five years from diagnosis, irrespective of disease recurrences. Review of the literature showed that more than 50% of cancer survivors with gynecological cancer still experienced health concerns/long-term side effects. Main side effects included neurologic symptoms, sleep disturbance, fatigue, sexual dysfunction, bowel and urinary problems and lymphedema. In this article, long-term side effects are discussed in detail and treatment options are proposed. Screening for second primary cancers and lifestyle counselling (nutrition, physical activity, mental health) may improve quality of life and overall health status, as well as prevent cardiovascular events. Clinical trials should address cancer survivorship and report patient reported outcome measures (PROMs) for cancer survivors. Conclusion: Long-term survivors after gynecological cancer have unique longer term challenges that need to be addressed systematically by care givers. Follow-up after completing treatment for primary gynecological cancer should be offered lifelong. Survivorship care plans may help to summarize cancer history, long-term side effects and to give information on health promotion and prevention.